Macroeconomic effects of public-sector unions - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Motivated by the highly-unionized public sectors, the high public shares in total employment, and the public-sector wage premia observed in Europe, this paper examines the importance of public-sector unions for macroeconomic theory. The model generates cyclical behavior in hours and wages that is consistent with data behavior in an economy with highly-unionized public sector, namely Germany during the period 1970-2007. The union model is an improvement over a model with exogenous public employment. In addition, endogenously-determined public wage and hours add to the distortionary effect of contractionary tax reforms by generating greater tax rate changes, thus producing higher welfare losses.
Keywords: E62; J51; 330; public sector labor unions; fiscal policy; public wages; public employment